Effect of a Low-Carbohydrate Diet With or Without Exercise on Anxiety and Eating Behavior and Associated Changes in Cardiometabolic Health in Overweight Young Women - Hu, Mingzhu; Shi, Qingde; Sun, Shengyan; Hong, Hin Ieong; Zhang, Haifeng; Qi, Fengxue; Zou, Liye; Nie, Jinlei (Frontiers in Nutrition, 2022)
Background: The effectiveness of low-carbohydrate diets (LCDs) on weight loss and exercise for improving cardiometabolic fitness have been well documented in the literature, but the effects of LCDs and whether adding exercise to a LCD regime could additionally benefit mental health (e.g. by lowering the level of anxiety) and associated changes in eating behaviour are less clear in overweight and obese populations. Therefore, this study aimed to investigate the effects of a 4-week LCD with or without exercise on anxiety and eating behaviour and explore the associations between changes in the psychological state and physiological parameters (i.e. body composition, aerobic fitness, blood pressure, lipid profile and metabolic hormones). Methods: Seventy-four overweight Chinese women (age: 20.8 ± 3.0 years, body mass index [BMI]: 25.3 ± 3.3 kg·m−2) completed the randomized controlled trial, which included a LCD group (i.e. ~50 g daily carbohydrate intake) with exercise (LC-EXE, n = 26), a LCD group without exercise training five days a week for 4 weeks (LC-CON, n = 25) and a control group that did not modify their habitual diets and physical activity (CON, n = 23). Levels of anxiety, eating behaviour scores and physiological parameters (i.e. body weight, V̇O2peak, blood pressure, fasting glucose, blood lipids, serum insulin, c-peptide, leptin and ghrelin) were measured before and after the intervention. Results: There were significant weight reductions (∆Weight = -3.0 ± 1.0 kg) and improvements in blood pressure in both LC-CON and LC-EXE groups after the 4-week intervention, but adding exercise to a LCD regime generated no additional effects. However, there were significant improvements in cardiovascular fitness and anxiety in the LC-EXE compared with the LC-CON group, while no statistical differences were found between CON and LC-CON treatments. Further analysis revealed a strong negative association (r = -0.32, p <0.01) between changes in levels of anxiety and changes in V̇O2peak in all participants. Conclusion: Although the combination of a LCD and exercise may not induce additional reductions in body weight in overweight young females, exercise could be a useful add-on treatment along with a LCD to improve cardiometabolic health and lower anxiety levels.